2008
DOI: 10.1007/s00027-008-8065-6
|View full text |Cite
|
Sign up to set email alerts
|

Responses of lake phytoplankton to micronutrient enrichment: a study in two New Zealand lakes and an analysis of published data

Abstract: Natural and anthropogenic changes in nutrient concentrations can affect phytoplankton in marine and freshwater environments. However, potential micronutrient limitation of phytoplankton productivity in fresh waters is often overlooked. To investigate the responses of lake phytoplankton to micronutrient enrichment, we conducted a study in two contrasting New Zealand lakes, and analysed data from the published international literature. We undertook nutrient enrichment bioassays of phytoplankton communities sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 54 publications
3
45
0
1
Order By: Relevance
“…Recent studies of Lake Erie phytoplankton (Moon and Carrick, 2007;North et al, 2007) have demonstrated limitation by nutrients other than P and N. Additionally, trace metal limitation has been documented in surface cyanobacterial blooms (Downs et al, 2008). Therefore, it is important to assess Microcystis micronutrient status in western Lake Erie.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of Lake Erie phytoplankton (Moon and Carrick, 2007;North et al, 2007) have demonstrated limitation by nutrients other than P and N. Additionally, trace metal limitation has been documented in surface cyanobacterial blooms (Downs et al, 2008). Therefore, it is important to assess Microcystis micronutrient status in western Lake Erie.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental Fe additions can trigger blooms of equatorial marine phytoplankton (Martin et al 1994, Coale et al 1996, but there is no evidence that Fe controls primary productivity at the ecosystem-level in freshwater. Instead, bottle-scale experiments have shown that Fe can be a proximate limiting nutrient of algal growth (Wurtsbaugh and Horne 1983, Twiss et al 2000, Downs et al 2008. In vitro and in vivo experiments have also shown that changes in Fe availability affect the outcome of competition among phytoplankton species (Pollingher et al 1995, Vuorio et al 2005, Molot et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Calculated fluxes of Co via groundwater discharge into West Neck Bay (Long Island, New York, USA) ranged from 3.4x10 2 μmol day −1 to 8.2x10 3 μmol day −1 , depending on sampling location and season. Other research has suggested that micronutrients, including B, Co, Cu, Fe, and Mo, can increase algal or cyanobacterial growth when concentrations of macronutrients (i.e., nitrogen and phosphorus) are already high and the system is already characterized as eutrophic (Zhang, 2000;Downs et al, 2008). As eutrophic conditions in coastal waters are expected to become more prevalent in the future (Rabalais et al, 2009), the role of metal micronutrients, including those associated with groundwater discharge, may become more important.…”
Section: Discussion 41 Dissolved Metal Fluxes Via Groundwater To Thementioning
confidence: 99%